1992
DOI: 10.1002/jbmr.5650070109
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass and body composition in normal women

Abstract: The interrelationships between measurements of bone mass and total-body bone mineral were examined in a cross-sectional study of normal healthy women aged 17-82 years. In addition we evaluated the relationship between measures of body composition, estimated by four independent techniques, and bone mass in the same population. Considering the group as a whole, bone mass at all sites correlated with each other and with total-body bone mineral (TBBM). Cancellous and cortical sites could predict TBBM equally well.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(30 citation statements)
references
References 22 publications
5
24
0
1
Order By: Relevance
“…Previous studies have shown that bone mass is associated with lean body mass because of the muscular forces leading to localized stresses on the bone, which then result in osteogenesis [11]. We examined the association between the change in lean body mass and changes in B-ALP from baseline to 20-week followup, but no correlation was found in either group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that bone mass is associated with lean body mass because of the muscular forces leading to localized stresses on the bone, which then result in osteogenesis [11]. We examined the association between the change in lean body mass and changes in B-ALP from baseline to 20-week followup, but no correlation was found in either group.…”
Section: Discussionmentioning
confidence: 99%
“…Both body weight and body fat distribution increase with a shift toward an android distribution, and there is a decrease in FFM. It is unclear whether the commonly observed postmenopausal changes of body composition are related entirely to ageing or are accelerated by estrogen deficiency (34). This is important because body FM and its distribution correlate with risks of coronary artery disease (5) and certain cancers (35), while lean body mass is associated with muscle strength, which correlates with the prevention of falls, frailty, and disability (36).…”
Section: Discussionmentioning
confidence: 99%
“…Higher body mass/increased mechanical loading may provide an osteogenic stimulus in non-smokers [41]. Body fat may provide a site for extraovarian aromatization of androgens to oestrogen [50,51]. Serum levels of the fat-derived hormone leptin correlated with bone mass at the spine, hip and total body in healthy non-obese women aged 20-91 years [52].…”
Section: Possible Mechanisms By Which Smoking May Affect Bmd and Fracmentioning
confidence: 93%